Penerapan Penyajian Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) (Studi Pada Toko Buku Media Insani Pontianak) - Sri Dewi Ayu Safitri Ayu; Tarina Dashela; Yeni Mustika; Mohammad Kamal Reza (LPPM Universitas Bina Sarana Informatika, 2025)
The application of accounting by presenting financial statements is one of the absolute things that must be owned if you want to continue to develop a business. The purpose of this study is to determine the application of the presentation of financial statements based on the financial accounting standards of entities without public accountability (SAK ETAP), as well as the obstacles faced in its implementation. This study uses qualitative research with a case study method. The steps taken to obtain data and information are through interviews and documentation.The results of this study indicate that the financial statements prepared by TB. Media Insani have not fully implemented the financial accounting standards of entities without public accountability (SAK ETAP) and this is due to the limited knowledge and human resources owned by TB. Media Insani.